2019
DOI: 10.1029/2019gl081981
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Frost Weathering Processes in Alpine Rockwalls

Abstract: Weathering processes prepare and trigger rockfall, which is a key agent of alpine landscape evolution and a hazardous process. The relative importance of different weathering processes is hard to decipher; nevertheless, current knowledge assumes a dominant role of frost cracking in eroding alpine rockwalls. This study uses a laboratory approach to simulate volumetric expansion and ice segregation in four alpine rock samples, monitors crack deformation, and quantifies frost weathering efficacy. Our results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
83
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 34 publications
1
83
0
Order By: Relevance
“…This observation has recently been substantiated by numerous field and lab experiments demonstrating intense frost cracking at temperatures just below 0 °C (Girard et al, 2013;Duca et al, 2014;Murton et al, 2016) and thermo-cryogenic rock fatigue due to damage accumulation over longer time scales (Jia et al, 2015). Subcritical stress propagation driven by sustained freezing and sufficient 345 water supply (Jia et al, 2017;Draebing and Krautblatter, 2019), and high plucking-related tensile stresses caused by refreezing meltwater at the bottom of the Randkluft (Lewis, 1938;Hooke, 1991). We hypothesize, therefore, that they are the dominant antecedent processes of rockfall preparation.…”
Section: Antecedent Rockfall Preparation Inside the Randkluftmentioning
confidence: 80%
“…This observation has recently been substantiated by numerous field and lab experiments demonstrating intense frost cracking at temperatures just below 0 °C (Girard et al, 2013;Duca et al, 2014;Murton et al, 2016) and thermo-cryogenic rock fatigue due to damage accumulation over longer time scales (Jia et al, 2015). Subcritical stress propagation driven by sustained freezing and sufficient 345 water supply (Jia et al, 2017;Draebing and Krautblatter, 2019), and high plucking-related tensile stresses caused by refreezing meltwater at the bottom of the Randkluft (Lewis, 1938;Hooke, 1991). We hypothesize, therefore, that they are the dominant antecedent processes of rockfall preparation.…”
Section: Antecedent Rockfall Preparation Inside the Randkluftmentioning
confidence: 80%
“…I assume that the rock samples are representative for the rockwall. For a more detailed description of the rock samples and their mechanical properties see Draebing and Krautblatter (2019). On each rock sample (Fig.…”
Section: Laboratory Measurementsmentioning
confidence: 99%
“…Current research highlights the role of mechanical weathering (Eppes and Keanini, 2017). Diurnal and seasonal ambient meteorological changes causing cyclic heating and cooling (Collins and Stock, 2016;Gunzburger and Merrien-Soukatchoff, 2011), wet-dry cycles (Zhang et al, 2015), freeze-thaw cycles (Matsuoka, 2001(Matsuoka, , 2008 or active-layer thaw (Draebing et al, 2017a;Draebing et al, 2014) produce critical and subcritical stresses that propagate micro-fractures (Draebing and Krautblatter, 2019;Eppes et al, 2018). Several studies investigated the influence of thermal changes on rockwalls and demonstrated the sudden erosion by thermal shock (Collins et al, 2019;Collins et al, 2018) and slow thermal-induced propagation of fractures in Alpine rockwalls (Weber et al, 2017;Hasler et al, 2012;Collins and Stock, 2016) that continuously weakens rock and can trigger rockfall (Ishikawa et al, 2004;Collins and Stock, 2016).…”
mentioning
confidence: 99%
See 2 more Smart Citations